TEMPORAL VARIATION IN CERATIUM SPP. ABUNDANCE RECORDED IN JAKARTA BAY - Thoha, Hikmah (Marine Research in Indonesia, 2012)
Ceratium is non-toxic dinoflagellate which has been regarded as the most common bloom-forming species in the coastal waters around the world. Eventhough research and monitoring on phytoplankton In Jakarta Bay have been conducted for long enough, no specific attention has been given to Ceratium community. Therefore, a research was set up in order to understand the dynamic of Ceratium population and its regulating factors. A serial sampling was conducted in 10 stations during 2009 and 2010. Phytoplankton was sampled in horizontal towing using Kitahara plankton net (80 ÃÂ¼m mesh size, 0.5 m mouth diameter and 1m length). Phytoplankton enumeration and identification were done by applying Fraction Method on Sedgewick Rafter Counting Chamber (SRCC). The result showed clear temporal variations in Ceratium absolute density, relative density, relative frequency and importance value. When phytoplankton bloomed in August 2009, no Ceratium bloom observed. High density of Ceratium was observed in November 2009 and May 2010, but it contributed relatively small proportion to phytoplankton as a whole (relative density <1%). Due to its low density and relatively limited distribution in Jakarta Bay, Ceratium may demonstrate limited ecological role to the phytoplankton community.